Coming to Terms With COVID-19 Reality in the Context of Africa’s Higher Education: Challenges, Insights, and Prospects - Osabwa, Wycliffe (Frontiers in Education, 2022)
This perspective paper aimed at elucidating the effects of the COVID-19 pandemic on African institutions of higher education. With specific reference to Kenya, the paper exposed the state of the country’s unpreparedness in terms of instructional technologies, a situation that had contributed to an almost total shutdown of institutions following the outbreak. It was notable that whereas Kenya had not borne the brunt of COVID-19 infections in comparison to other countries outside the continent, its education sector was adversely affected. This followed the social distancing requirement that limited in-person gatherings, implying that its learning institutions, which largely operated on in-person mode, had to close, the low infections notwithstanding. Since most universities in Africa had hitherto operated on this mode, the shift to online learning was not easy. Save for a few that had digital infrastructure, the rest encountered difficulties in moving to remote learning. Many had to quickly assemble digital curricula, the quality of which could not be guaranteed. Even if an institution managed to do so, not all students could be brought on board. Digital exclusion became more pronounced than ever before, with learners who were economically, technologically and geographically disadvantaged missing out. Inequalities in education were laid bare and exacerbated. All this notwithstanding, Africa learnt lessons. The whole experience prompted various stakeholders – university management, faculty and government – to rethink their modes of education delivery, with quality and access in mind. In retrospect, the pandemic could serve as a catalyst for digitalization in Africa’s higher education system.